Commentaries on viewpoint: Hoping for the best, prepared for the worst: can we perform remote data collection in sport sciences? - Louis, J.; Bennett, S.; Owens, D. J.; Tiollier, E.; Brocherie, F. (Journal of Applied Physiology, 2022)
Remote data collection (1) is of growing interest, especially in sport nutrition, whereby a specific diet and/or supplement is prescribed in conjunction with exercise training. Verifying adherence to prescribed interventions and estimation of dietary intake is paramount. Food diaries, dietary recall, and remote food photography methods (2) are already commonplace for monitoring dietary intake with the integration of training data (i.e., power output, heart rate) collected from online platforms (e.g., TrainingPeaks, Strava) connected to participants` own sports equipment (3) permitting the estimation of daily energy expenditure remotely (4). Researchers may therefore bridge the gap between laboratory and techniques classically used in field situations without the need for expensive laboratory equipment. It may also facilitate greater participation and compliance. For example, in a study by Bennett et al. (3), 495 training sessions and 165 testing sessions were performed remotely by 55 participants within a 2-mo period of national lockdown due to the COVID-19 pandemic. However, it is important to ensure that standardization and quality control are maintained across all participants, by providing clear instructions and frequent contact points. Familiarization sessions should be scheduled and used to verify the reliability of procedures. It is also recommended that all training and dietary intake data be visually inspected (i.e., review raw data) to ensure that protocols are followed correctly. Finally, when additional metabolic or body composition measurement is required, we suggest combining online training and nutritional prescription with laboratory-based testing (5). At a time where we all need to reduce our carbon footprint, remote data collection appears more relevant than ever.